The city of the moon god : religious traditions of Harran - Green, Tamara M. (Religions in the Graeco-Roman World, 1992)
This study treats the religious and intellectual history of the city of Harran (Eastern Turkey) from biblical times down to the establishment of Islam. The author starts from the well-known reference in the Qur'an and the early Islamic histories to the people of Harran as Sabians, one of the 'peoples of the book.' The author unravels strands of religious tradition in Harran that run from the old Semitic planetary cults through Hellenistic hermeticism, gnosticism, and Neo-Pythagoreanism and Christian cults to esoteric Islamic sects such as the Sufis and Shiites.